TermComp Proposal: Pushdown Systems as a Model for Programs with Procedures - Brockschmidt, Marc; Rybalchenko, Andrey (2014)
A program with procedures can be formally modelled by a set of transition relations that form a pushdown system. These transition relations keep track how valuations of variables in scope of individual procedures evolve during program execution. We present such a model together with its representation using the SMTLIB2 language.